(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
this article describes in detail the legal status, purpose, tasks and main directions of the prosecutor’s office, as well as the legal documents that are important in the organization of the prosecutor’s office.